Slow stitch : mindful and contemplative textile art - Wellesley-Smith, Claire (London : Batsford, 2015)
Introduction -- Slow -- Materials and techniques -- Cross-cultural activity -- Contemplative -- Conclusion
Sometimes less is more. That's true in textile art too, and this much--needed guide brings a meaningful, sustainable approach to stitchery. Slow down and experience more joy in your craft by trying simple techniques based on traditional practice, reusing and reinventing materials, and limiting equipment
Literaturverzeichnis: Seite 125
Keywords: Textile crafts